2020
DOI: 10.3390/ijms21155581
|View full text |Cite
|
Sign up to set email alerts
|

α1AMP-Activated Protein Kinase Protects against Lipopolysaccharide-Induced Endothelial Barrier Disruption via Junctional Reinforcement and Activation of the p38 MAPK/HSP27 Pathway

Abstract: Vascular hyperpermeability is a determinant factor in the pathophysiology of sepsis. While, AMP-activated protein kinase (AMPK) is known to play a role in maintaining endothelial barrier function in this condition. Therefore, we investigated the underlying molecular mechanisms of this protective effect. α1AMPK expression and/or activity was modulated in human dermal microvascular endothelial cells using either α1AMPK-targeting small interfering RNA or the direct pharmacological AMPK activator 991, prior to lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…AMPK is primarily known to regulate the energy requirements of the cell, but has also been implicated in other seemingly unrelated cellular processes such as migration, cell growth and apoptosis ( Hardie, 2011 ). This protein kinase has been studied previously in relation to its protective role at the BBB, in particular when challenged by LPS ( Takata et al, 2013 ; Zhao et al, 2014 ; Ange et al, 2020 ), whereas in the retinal pigment epithelium it has been shown to be responsible for permeability induced by IL-1β ( Villarroel et al, 2011 ). However, all these studies address chronic changes and do not focus on the role of AMPK for acute permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK is primarily known to regulate the energy requirements of the cell, but has also been implicated in other seemingly unrelated cellular processes such as migration, cell growth and apoptosis ( Hardie, 2011 ). This protein kinase has been studied previously in relation to its protective role at the BBB, in particular when challenged by LPS ( Takata et al, 2013 ; Zhao et al, 2014 ; Ange et al, 2020 ), whereas in the retinal pigment epithelium it has been shown to be responsible for permeability induced by IL-1β ( Villarroel et al, 2011 ). However, all these studies address chronic changes and do not focus on the role of AMPK for acute permeability.…”
Section: Discussionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) is a phylogenetically conserved energy sensor that regulates energy homeostasis by coordinating metabolic pathways and thus balancing energy requirement with nutrient supply ( Hardie, 2018 ). Previous studies suggest that AMPK acts as a protector of BBB integrity, for instance by preventing lipopolysaccharide (LPS)-enhanced NAD(P)H oxidase expression in ECs and the consequent barrier dysfunction and enhanced permeability ( Zhao et al, 2014 ; Ange et al, 2020 ). Moreover, AMPK mediates upregulation of BBB functions induced in vitro by metformin, a drug used for the treatment of diabetes ( Takata et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our team and others have previously demonstrated the pivotal role of α1AMPK in the maintenance of endothelial barrier function, in models of endotoxemia 5 , 26 , 27 . In mechanistic terms, we demonstrated that endothelial barrier protection by α1AMPK was mediated by p38MAPK/HSP27-dependent enhancement of VE-Cad stability 25 . Nevertheless, none of the AMPK activators used in the different studies can be safely employed in vivo or securely administered to septic patients 5 , 8 , 27 , 28 .…”
mentioning
confidence: 85%
“…The catalytic subunit of AMP-activated protein kinase (AMPK) is primarily expressed under its α1-isoform within the microvascular endothelium; there, it acts as a major regulator of the actin cytoskeleton and IEJs 23 25 . Our team and others have previously demonstrated the pivotal role of α1AMPK in the maintenance of endothelial barrier function, in models of endotoxemia 5 , 26 , 27 .…”
mentioning
confidence: 99%
“…Similarly, TAB1-p38 drives T-cell senescence via an AMPK-dependent regulatory pathway, resulting in downregulation of TCR signalosome [ 197 ]. AMPK also plays an essential role in the TAB1-p38 activation of HSP27 in simulated sepsis, maintaining vascular integrity [ 191 ]. Intracellular infection leading to TAB1-p38 activity was first shown in macrophages in mice infected with Toxoplasma gondii, resulting in pro-inflammatory IL-12 production specific to atypical signaling [ 189 ].…”
Section: Pathophysiological Implications Of Atypical P38 Signalingmentioning
confidence: 99%